924. Cytomegalovirus (CMV) Retinitis during Maintenance Chemotherapy for Acute Lymphoblastic Leukemia. (4th December 2021) - Yoke, Leah H; Boeckh, Michael; Banda, Himanshu; Kimble, Erik L; Martino, Christen; Cassaday, Ryan; Zamora, Danniel
Abstract: Background: Acute leukemia patients are at risk for cytomegalovirus (CMV) retinitis following hematopoietic stem cell transplantation, though the disease can also occur in non-transplant adult leukemia patients. Emerging data suggest a shift to pediatric-inspired chemotherapy regimens in adults with acute lymphoblastic leukemia (ALL) can lead to increasing cytopenias and impaired functional immunity, placing these patients at risk for this opportunistic infection. Here we describe a case of CMV retinitis in an ALL patient following a lower-intensity regimen during maintenance chemotherapy. Methods: Chart review. Results: A 55-year-old male with ALL presented to his optometrist with complaints of visual changes including "fogginess" and "floaters". The patient had completed 8 cycles of dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab (EPOCH-R) and achieved complete remission. He had been on maintenance chemotherapy with 6-mercaptopurine, vincristine, methotrexate, and prednisone (POMP) for 2 months at the time of symptom onset. He was referred to his local ophthalmologist who had concerns for bilateral, zone 1 CMV retinitis based on fundoscopic exam (Figure 1). Vitreous aspiration was performed and CMV DNA PCR returned positive at 1.6 million IUs/ml. Peripheral blood CMV DNA PCR was also positive at 1133 IU/ml. He was started on combination therapy with intravitreal ganciclovir injections and oral valganciclovir 900 mg twice daily (Figure 2). The patient received 14 intravitreal injections with resultant stability of his eye exam, though he remained on induction valganciclovir for 5 months due to persistent blood CMV DNAemia. Letermovir was added to help suppress his peripheral CMV DNAemia and he attained partial vision recovery. Figure 1. Fundoscopic images Conclusion: CMV retinitis is an uncommon and highly morbid infection that can occur during maintenance chemotherapy in adult non-transplant ALL patients. Early identification of the disease is imperative as delay can result in blindness or further systemic CMV disease. Treatment is challenging, involving systemic and intravitreal antiviral therapy, serial ophthalmologic exams, serum CMV monitoring, and close coordination with the treating hematologist. Disclosures: Michael Boeckh, MD PhD, AlloVir (Consultant)Ansun Biopharma (Grant/Research Support)Astellas (Grant/Research Support)EvrysBio (Consultant, Other Financial or Material Support, Options to acquire equity, but have not exercised them)Gilead Sciences (Consultant, Grant/Research Support)GlaxoSmithKline (Consultant)Helocyte (Consultant, Other Financial or Material Support, Options to acquire equity, but have not exercised them)Janssen (Grant/Research Support)Kyorin (Consultant)Merck (Consultant, Grant/Research Support)Moderna (Consultant)Symbio (Consultant)Takeda (formerly known as Shire ) (Consultant, Grant/Research Support)VirBio (Consultant, Grant/Research Support) Ryan Cassaday, MD, Amgen (Grant/Research Support, Advisor or Review Panel member)Kite/Gilead (Grant/Research Support, Advisor or Review Panel member)Merck (Grant/Research Support)Pfizer (Grant/Research Support, Advisor or Review Panel member)Seagen (Other Financial or Material Support, Spouse is employee and hold stock)Vanda Pharmaceuticals (Grant/Research Support)